Uthållig sanitet - Ericsson, Niclas (2005)
The access to good sanitary facilities is an important factor that elevates the experienced living standard as it improves hygiene and reduces the transmission of deseases. The ratification of the millennium goals by 189 countries demonstrates that this is an important international issue. Together the countries have taken upon themselves that the proportion of the population that lacked access to sustainable safe drinking water and sanitary facilities in the year 2000 will have been reduced by half by the year 2015.